Trying to Rise in Turmoil: Normalization of Semarang PortDuring the Indonesian Revolution Period - Maulida, Faishal Hilmy (Journal of Indonesian History, 2024)
port was mainly used for military purposes, as a result, many of the facilities and infrastructure of this port were not maintained and suffered much damage. Through this research, we will explain the efforts made by the Dutch occupation government to normalize ports so they can operate for commercial purposes. This research applies a historical approach involving four main stages: (1) heuristics, which includes collecting data through books, newspapers and oral sources in the field; (2) verification, which focuses on criticism of those sources; (3) interpretation, or the process of interpreting data; and (4) historiography, namely the presentation of research results. Through this research, the results obtained are that there were improvements to the Port of Semarang during the Revolutionary period, preceded by collecting data on damage to the port, repair efforts, and normalization of port activities. This research concludes that the Port of Semarang became commercially active again during the Revolution after the Dutch government, which occupied the area, normalized port operations. This differs from the Japanese occupation period, where the port was more often used for military purposes.